The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c4nr04970e
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of nanoparticle cytotoxicity approaching in vivo serum concentrations: limitations of in vitro testing for nanosafety

Abstract: Nanomaterials challenge paradigms of in vitro testing because unlike molecular species, biomolecules in the dispersion medium modulate their interactions with cells. Exposing cells to nanoparticles known to cause cell death, we observed cytotoxicity suppression by increasing the amount of serum in the dispersion medium towards in vivo-relevant conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 34 publications
8
86
0
Order By: Relevance
“…Also, Wang et al have shown that the protein corona protects the cells from damage until the corona proteins are degraded within lysosomes [63]. We observed that the membrane damage induced by 25 nm SNPs in serum-free medium was reduced not only by addition of serum, like also observed by Kim et al [64], but also after addition of single-serum proteins like BSA (bovine serum albumin) (Additional file 5). These results agree well with the research performed by Gualtieri et al which revealed a reduced cytotoxicity of SNPs in the presence of BSA and demonstrated that the surface coating of the particles is primarily responsible for the protective effect [62].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Also, Wang et al have shown that the protein corona protects the cells from damage until the corona proteins are degraded within lysosomes [63]. We observed that the membrane damage induced by 25 nm SNPs in serum-free medium was reduced not only by addition of serum, like also observed by Kim et al [64], but also after addition of single-serum proteins like BSA (bovine serum albumin) (Additional file 5). These results agree well with the research performed by Gualtieri et al which revealed a reduced cytotoxicity of SNPs in the presence of BSA and demonstrated that the surface coating of the particles is primarily responsible for the protective effect [62].…”
Section: Discussionsupporting
confidence: 81%
“…This should be taken into account when comparing results of different studies. In comparison to other studies using commercial nanoparticles or even larger particles [11, 64], the nanoparticles used in this study were custom-made, corroborating the generality of the protective effect of the protein corona.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, nanoparticle size and crystalline structure have been studied as underlying characteristics for nanoparticle toxicity. 2730 TEM images demonstrated that anatase TiO 2 nanoparticles had the characteristic spherical crystal structure while rutile nanoparticles had typical rod-like crystal structure (Fig 1). The anatase and rutile TiO 2 nanoparticles utilized for this study were both reported as 50 nm in diameter by the manufacturer, thus allowing for observations of crystal structure influence on nanoparticle toxicity independent of particle size.…”
Section: Resultsmentioning
confidence: 98%
“…In last few years a wide range of nanoformulations have emerged although their translational impact overall has been disappointing with poor in vitro -in vivo correlation [128][129][130]. There are challenges in characterization of NPs under physiologically relevant conditions.…”
Section: Discussionmentioning
confidence: 99%